PENGOLAHAN SAMPAH ORGANIK MENJADI KOMPOS UNTUK MENDUKUNG KAMPUNG PRO IKLIM - Normela Rachmawati; Susilawati Susilawati; Eva Prihatiningtyas (Universitas Islam kalimantan MAB, 2019)
Trash is a major problem in Banjarbaru City thus far. The trash volume in Banjarbaru approximately 120 tons per day on year 2017-2018 and that goes to landfill thereabouts 105 tons. Therefore, it is important manage the household waste, so do on community level through